Effective sexual health interventions issues in experimental evaluation - Stephenson, Judith M.; Bonell, Chris; Imrie, John, 1960- (Oxford : Oxford University Press, 2003)
This text provides an analysis of the methodological and practical issues involved in evaluating sexual health interventions. It should appeal to trial enthusiasts through discussion of specific issues in trial design, and also to those with a sceptical interest in the potential of experimentation.
Description based on print version record.
Keywords: Reproductive health; Hygiene, Sexual; Sexology